In sacco dry matter and nitrogen degradation and their relationship with in vitro dry matter digestibility of Napier grass (Pennisetum purpureum Schumach) as influenced by height of plant at cutting - Zewdu, T.; Baars, R.; Yami, A.; Negassa, D. (Commonwealth Scientific and Industrial Research Organisation, 2002)
In vitro dry matter digestibility (IVDMD) as well as in sacco rumen dry matter degradability (DMD) and nitrogen degradability (ND) studies of Napier grass (Pennisetum purpureum) were carried out using a 3 X 3 factorial experiment arranged in a randomised complete block design with 3 replications. The treatments were 3 levels of nitrogen (N) fertiliser (0, 46, and 92 kg/ha) and 3 heights at cutting (cutting was done when the grass reached 0.5, I, and 1.5 m above the ground). The N fertiliser treatment did not yield any significant difference in DMD, ND, or IVDMD. Height at cutting had a significant (P < 0.05) effect on rumen DMD and ND and their degradability characteristics for all incubation times., There was a reduction in DMD and ND and their degradability characteristics as plant height increased at cutting. Similarly, as height at cutting increased there was a decline in IVDMD. There was a positive linear correlation between IVDMD and both DMD and ND at 48, 72, 96, and 120 h (r = 0.917, 0.923, 0.921, and 0.850 for DMD; r = 0.795, 0.814, 0.787, and 0.787 for ND). Hence, further study on intake and performance of animals is suggested to develop Napier-based diets for smallholders.